2015
DOI: 10.1371/journal.pone.0130677
|View full text |Cite
|
Sign up to set email alerts
|

Potential Role of Circulating microRNA-21 for Hepatocellular Carcinoma Diagnosis: A Meta-Analysis

Abstract: BackgroundCirculating microRNA-21 (miR-21) is known to be aberrantly expressed in hepatocellular carcinoma (HCC) patients, and this implies that microRNA-21 is a promising and novel indicator of HCC. However, a systematic evaluation of the performance of microRNA-21 as a diagnostic marker for HCC has yet to be conducted. Therefore, the test performance of circulating miR-21 for HCC was assessed in this study.MethodsThree common international databases and a Chinese electronic database were used to search for l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 35 publications
0
26
0
Order By: Relevance
“…MiR-21, one of the most studied miRNAs, has been widely reported for its over-expression in various cancer types, and has also been found in extracellular environment [10, 1214, 77]. In the present study, we performed a meta-analysis of 7494 participants derived from 81 published studies worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-21, one of the most studied miRNAs, has been widely reported for its over-expression in various cancer types, and has also been found in extracellular environment [10, 1214, 77]. In the present study, we performed a meta-analysis of 7494 participants derived from 81 published studies worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, serum miR-21 levels are also increased in patients with different liver diseases, namely chronic viral hepatitis, as well as in other human cancers, such as gastric and colorectal cancer [ 112 , 113 ]. In fact, although increased expression of miR-21 may not be specifically associated with HCC alone, a recent study showed that circulating miR-21 may serve as a potential co-biomarker for early-stage HCC diagnosis [ 114 ]. Tomimaru et al also suggested that the combination of plasma miR-21 and AFP has a better differentiating power than miR-21 or AFP alone in discriminating HCC from healthy volunteers [ 111 ].…”
Section: Putative Circulating Mirnas In Nafld To Hcc Progressionmentioning
confidence: 99%
“… 51 At the same time, miR-21 had been confirmed to be regarded as a marker for early diagnosis of liver cancer. 52 Although there are a considerable number of studies on miRNAs in HCC, and it also shows the relationship between the diagnosis, metastasis and prognosis of HCC, but there is no report about the expression of miR-4463.…”
Section: Discussionmentioning
confidence: 99%